Approximate method for solving strongly fractional nonlinear problems using fuzzy transform - Firozja Mohamad Adabitabar; Agheli Bahram (Nonlinear Engineering, 2019)
In this research work, we have shown that it is possible to use fuzzy transform method (FTM) for approximate solution of strongly fractional nonlinear problems. In numerical methods, in order to approximate a function on a particular interval, only a restricted number of points are employed. However, what makes the F-transform preferable to other methods is that it makes use of all points in this interval. The comparison of the time used in minutes is given for two derivatives Caputo derivative and Caputo-Fabrizio derivative.